Актуальні проблеми формування та розвитку персоналу підприємств - Копець, Г. Р. (Видавництво Львівської політехніки, 2011)
На основі сучасних тенденцій функціонування підприємств обґрунтовано необхідність проведення досліджень та удосконалення у сфері розвитку людських ресурсів підприємств. Розвиток людських ресурсів є важливим елементом конкурентних переваг підприємств. Окреслено перспективи подальших досліджень. On the basis of current trends in enterprises operation the necessity of conducting research and improving in the field of the human resourses of the enterprises is grounded. Growth of human capitals is the important element of competitive edges of enterprises. Prospects of subsequent researches are outlined.
Actual problems of forming and growth of human resources of the enterprises
Keywords: розвиток людських ресурсів; мотивація персоналу; ефективне управління персоналом; growth of human capitals; motivation of personnel; effective management of the personnel